Uma sequência didática para o ensino do tema: “produção e consumo de energia elétrica”. - Azevedo, Renata Correia de (2021)
This dissertation aims to describe the elaboration, application, and results generated by a didactic sequence for the teaching of the theme production and consumption of electric energy, in a third grade class of the high school of the public school system of the State of São Paulo. The didactic sequence aimed at cognitive development and critical thinking of students on the theme of production and consumption of electricity. To make this possible, different teaching strategy were applied, among them: conceptual map, seminar, research, debate, case study, and simulated jury. Using the concepts of Antoni Zabala (1998) and Vygotsky's historical-cultural theory in the process of foundation and development, the didactic sequence sought to potentiate the cognitive advances of the students before the theme, facilitating the teaching-learning process. The theoretical-scientific foundation, together with the selected teaching strategies, were essential for the CTSA (Science, Technology, Society and Environment) approach when seeking to develop a critical sense in students before the concept worked. During the application and analysis of the results, evidence was found that the theoretical references of teaching together with the different teaching strategies proved to be efficient since the students demonstrated throughout the activities a better understanding of the concepts worked.